Nature of Relationship between Reverse Logistics and New Product Development at Pharmaceutical Industry - Salas, E (2010)
The development of more efficient logistic systems is crucial in this increasingly globalized world to obtain competitive advantage. In addition, the recovery of used products and materials has had more attention because among other factors, the increasing collective interest of protecting the environment and the reduction of expenditures are an important issue worldwide. In order to face these challenges, research areas such as Reverse Logistics have being studied and developed.